Adverse childhood experiences and hypertension: examining the roles of depressive symptoms and cardiometabolic dysregulations based on CHARLS data - Huang, Xuemei; Song, Huiqiong; Liu, Shuyang; Gong, Limeihui; Miao, Rui (Frontiers in Public Health, 2025)
ObjectiveThis study aims to explore the relationship between Adverse Childhood Experiences (ACEs), depressive symptoms, and cardiometabolic dysregulations in the context of hypertension risk, while examining both psychological and physiological factors contributing to the development of hypertension.MethodsProspective data were sourced from the China Health and Retirement Longitudinal Study (CHARLS). The data used in this study were collected from the baseline survey in 2011, with follow-up data obtained in 2013 and 2015, covering a 4-year period. Depressive symptoms and cardiometabolic dysregulations were derived from the 2011 baseline survey. Data on ACEs were obtained from the 2014 survey. Incident hypertension cases were defined as new cases of hypertension during the follow-up period (2013 and 2015) among participants who were not hypertensive in 2011. A univariate logistic regression analysis was conducted for correlation analysis, and a path analysis using structural equation modeling (SEM) was performed. The total baseline sample consisted of 6391 participants, with 434 new cases of hypertension during the follow-up period.ResultsThe study found that 50.23% of the population had experienced at least one ACE. ACEs were associated with an increased risk of hypertension, Each additional ACE raised the odds of developing hypertension based on systolic blood pressure by 25.2% (OR 1.252 [95% CI 1.103, 1.648], p = 0.014). No significant association was observed with diastolic blood pressure. The SEM indicated that ACEs did not have a direct effect on hypertension. Instead, the relationship was mediated by depressive symptoms and cardiometabolic dysregulations. The indirect effect along the ACEs → cardiometabolic dysregulations → SBP pathway was 0.066 (95% CI 0.002, 0.105, p = 0.002), and for the ACEs → cardiometabolic dysregulations → DBP pathway, the coefficient was 0.013 (95% CI 0.003, 0.124, p = 0.002).The study found no evidence supporting depressive symptoms as a significant mediator.ConclusionACEs show a positive association with hypertension occurrence. They may contribute to hypertension development through their influence on cardiometabolic dysregulations.